A comparison of different test and analysis methods for asphalt fatigue - Maggiore, Cinzia (2014)
Flexural fatigue is one of the main failure modes in asphalt mixtures. After reviewing and critiquing the current literature about fatigue in pavement engineering, this research project focused on dissipated energy approach because it takes into account the evolution of the material during a test. A comparison between the traditional method and several dissipated energy methods was made by using statistical analysis.